2022
DOI: 10.1186/s12889-022-12586-2
|View full text |Cite
|
Sign up to set email alerts
|

Substance use in childhood and adolescence and its associations with quality of life and behavioral strengths and difficulties

Abstract: Background Substance use in childhood and adolescence continues to be a current health concern. The aims of the present study were to identify trends in the use of alcohol, cigarettes, and cannabis in children and adolescents in the last 10 years and to assess associations between substance use and quality of life and behavioral strengths and difficulties. Methods Substance use was examined in 1829 9- to 18-year-old German children and adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
1
5
0
1
Order By: Relevance
“…We found correlations between cannabis use and externalizing behavioral di culties (conduct problems), SDQ total di culties and low prosocial behavior. Our results are consistent with those found in other works suggesting that early-onset persistent conduct problems were associated strongly with problem cannabis use and that cannabis use can be viewed as an indicator of risk for mental health problems in adolescence [58,59]. We also found a positive correlation between other substances (sedatives and hallucinogens) and internalizing behavioral di culties (peer problems), which could indicate a different psychological pro le with the use of less common substances as possible coping strategies for internalizing problems [60,61].…”
Section: Discussionsupporting
confidence: 93%
“…We found correlations between cannabis use and externalizing behavioral di culties (conduct problems), SDQ total di culties and low prosocial behavior. Our results are consistent with those found in other works suggesting that early-onset persistent conduct problems were associated strongly with problem cannabis use and that cannabis use can be viewed as an indicator of risk for mental health problems in adolescence [58,59]. We also found a positive correlation between other substances (sedatives and hallucinogens) and internalizing behavioral di culties (peer problems), which could indicate a different psychological pro le with the use of less common substances as possible coping strategies for internalizing problems [60,61].…”
Section: Discussionsupporting
confidence: 93%
“…Remaja yang mandiri dapat mengembangkan empati sehingga berdampak pada penurunan cyber-bullying (Fousiani et al, 2016). Kualitas hidup remaja yang salah satunya dilihat dari parent relation and autonomy dapat menurunkan kecenderungan konsumsi rokok dan ganja (Frobel et al, 2022). Parental autonomy support yang diperoleh remaja dapat menjadi buffer terhadap depresi, kecemasan, dan stres (Liu et al, 2022).…”
Section: Latar Belakangunclassified
“…Scientific evidence has shown that school and family are the most influential agents of primary socialization. School can either protect or pose a risk to the development of problem behaviors ( 10 , 11 ) and the use of alcohol, tobacco, and cannabis ( 12 , 13 ). Greater school commitment has been negatively related to substance use and being involved in fights ( 14 ).…”
Section: Introductionmentioning
confidence: 99%